FAKTOR-FAKTOR YANG MEMPENGARUHI INFEKSI TB PADA ANAK YANG TINGGAL SERUMAH DENGAN PENDERITA TB - LIUNOKAS, OKLAN BT (JURNAL KESEHATAN PRIMER, 2016)
Introduction: the disease of tuberculosis is still a major problem faced by most of the people of the world especially in developing countries. Prevalence of pulmonary TUBERCULOSIS in the community because of the alleged risk of transmission still remains large, especially the transmission because the same house contact with Pulmonary TB sufferers. The research aims to find out the factors that influence infection of TB in children 0-18 years who are in contact with sufferers of the same House. Methods: this research is quantitative research with cross sectional design performed in Clinics Waingapu, East Sumba. By taking a sample of children aged 0-18 years the same House with Pulmonary TB sufferer BTA (+) amounted to 55. Data collection is done with the interview, observation and measurement of the nutritional status of the child and a density of residence. Results: the level of knowledge of respondents with the chi square analysis Asymp. Sign. (2-sided) = 0,043 Ha α = 0,043 < < 0.05, family behavior when coughing by 0,016 = Ha = α < 0,016 < 0.05, nutritional status of families 0,020 = Ha = 0,020 < 0.05 family residences and a density of toddlers with 0,004 = α = 0,004 Ha < < 0.05. Conclusion: preventive behavioral factors of tuberculosis, nutritional status and a density of residential as a factor that influences the occurrence of TB infection in children who are in contact with sufferers in the same House Clinics Waingapu.